Perilaku Laju Perambatan Retak Fatik Pada Hasil Pengelasan Tig Al 6061 â T4 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRAK Fatigue crack growth rate of T1G welding joint of Al 6061 â T4 has been investigated. The tests were performed in a room temperature with a constant load amplitude and the load ratio was maintained to be 0,1. The load frequency was adjusted in the range of / â I 1 Hz. Crack propagation tests were carried out on 1.6 mm thick of center crack tension (CO) specimens with longitudinal and transversal bun joints. Alternating current manual TIG welding has been set in 5 nmvs traveling speed, 10 volt, 60 A current, with 1,6 mm filler diameter. The filler wire used in this research was Al 4043. The experimental result shows that crack growth rate on HAZ zone of transversal but joint increases the Paris constant's n from 3,43 to 3,7 or about 9 % and C from 6,39 x 10-n to 2,63 x /0 0. Paris constant's n of fatigue crack growth rate on weld zone decreases about 10 %. On longitudinal butt joint crack growth rate, the CGR is increased when the crack tip is acrossing the weld zone. Transversal butt joint reduces the tensile strength of Al 6061 â T4 about 39 % and elongation about 81,5 %. The tensile strength of longitudinal butt joint decreases about 25% Filler's compositions Al 4043 increases composition of Si in the weld zone become 2,27%.